Effect of conjugation length on the properties of fused perylene diimides with variable isoindigos. Issue 39 (25th September 2019) - Yu, Yaping; Xue, Ning; Xiao, Chengyi; Ravva, Mahesh Kumar; Guo, Yanjun; Wu, Liyun; Zhang, Lei; Li, Zhengke; Yue, Wan; Wang, Zhaohui
Abstract : We have synthesized a series of fused hybrid perylene diimides and isoindigos, and investigated their structure–property relationships. Abstract : We have successfully synthesized four fused hybrid diimide and diamide arrays with different effective conjugation lengths of perylene diimides and isoindigos. These arrays with varying numbers of amides and imides are an efficient strategy to fine-tune the opto-electronic properties, conformation, energy levels and device performance. It is shown that additional fused isoindigos lead to much lower electron affinity with no influence on the ionic potential. The impact of adding different additional central electron deficient isoindigos to the fused arrays has also been investigated systemically. PDI-BDOPV-PDI incorporating a strong electron deficient BDOPV unit with enforced coplanarity exhibits a very low lowest unoccupied molecular orbital (LUMO) level of −4.11 eV, and the absorption spectrum of PDI-DPN-PDI was even extended to 1000 nm. Thin film transistors were fabricated with these arrays as the semiconductor layers, the fused arrays display electron transport behaviors.